ASSESSING THE EFFICACY OF SYSTEMIC IMMUNOSUPPRESSIVE THERAPIES IN TREATING SEVERE ECZEMA. A SYSTEMATIC REVIEW AND META-ANALYSIS - Arzu Khattak; Moustafa H A Hamada; Latifa Al Abdal; Shaikha Mohammed M Alqahtani; Shamsa Bin Bader Alaleeli; Dhoha Mohamed Ahmed Alsalmi; Reem Ahmed Abdelrahman Eldoma; Kuer Mabil; Alqahtani Rose Fayiz M; Sumayyah Leila Zaman; Nuha Yassir Jassim (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Severe eczema refers to atopic dermatitis (AD) which results in long-lasting chronic inflammatory skin condition that creates severe effects on patient life quality. Systemic immunosuppressive therapies become essential for treating severe cases but they serve alongside topical treatments for treating mild-to-moderate conditions. The evaluation of both effectiveness and security outcomes for these treatments enables optimal medical treatment for patients. Objectives: The present systematic assessment evaluates the treatment impact and safety levels of systemic immunosuppressive drugs for severe eczema as it reviews multiple therapeutic agents and presents evidence-backed clinical practice guidelines. Methodology: The research examined databases of PubMed and Cochrane Library and Embase from the period between 2015 and 2024 for available studies. A research analysis included Randomized Controlled Trials (RCTs) and systematic reviews and meta-analyses of systemic immunosuppressive drugs which included cyclosporine along with methotrexate and azathioprine and mycophenolate mofetil and biologic therapeutics. The studies provided information about treatment effectiveness which included Eczema Area and Severity Index (EASI) scores together with Investigator’s Global Assessment (IGA) and patient-reported outcomes and general security profiles. Results: The selected studies numbered twenty-five. Brands such as dupilumab and JAK inhibitors including upadacitiniband abrocitinib exceeded expectations in their effectiveness and showed beneficial safety aspects above traditional immunosuppressant medicines that include cyclosporine and methotrexate. The traditional treatment approaches remained effective yet produced more adverse events that harmed the kidneys and liver functions. The addition of systemic therapy with topical corticosteroids as combination treatment yielded better results while minimizing new adverse reaction risks. Conclusion: The management of serious eczema cases depends on systemic immunosuppression treatments. The therapeutic shift in eczema treatment now includes, biologic agents together with targeted therapies because they demonstrate superior efficacy and safety compared to traditional immunosuppressant. The selection of systemic treatments for patients requires clinicians to assess individual patient health conditions and their established therapeutic objectives.